Cohesive zone and interfacial thick level set modeling of the dynamic double cantilever beam test of composite laminate. (August 2018) - Liu, Y.; van der Meer, F.P.; Sluys, L.J.
Highlights: Rate-dependent CZM can capture the average crack growth speed in dynamic tests. The investigated rate-dependent CZM cannot reproduce crack arrest. The ITLS method is extended to simulate delamination under dynamic loading. The ITLS model can capture "stick/slip" crack growth including crack arrest. Abstract: The mode-I interlaminar fracture toughness of composite laminates under different loading rates can be measured by the double cantilever beam (DCB) test. It is observed from the DCB test of a unidirectional PEEK/carbon composite laminate that as the loading rate increases from quasi-static to dynamic range: (1) delamination crack growth exhibits a transition from stable to unstable ("stick/slip") and back to a stable type; (2) the interlaminar fracture toughness is not constant as the loading rate increases. In this paper, two numerical approaches are used to reproduce the experimental observations: a cohesive zone model (CZM) and the interfacial thick level set (ITLS) model. CZM simulations with rate-independent and rate-dependent cohesive laws are carried out. A new version of the ITLS is introduced with a phenomenological relation between crack speed and energy release rate. The simulation results of the CZM and the ITLS model are compared with the real DCB test data to evaluate the capability of these two types of models. It is found that the used CZM can reproduce rate-dependence of the fracture energy, but not the stick/slip behavior. The ITLS can capture the stick/slip behavior, but needs different parameter sets for different loading rates.